The first case of induced gynogenesis in Neotropical fishes using the yellowtail tetra (Astyanax altiparanae) as a model organism - Nascimento, Nivaldo Ferreira do [UNESP]; Monzani, Paulo Sergio; Pereira-Santos, Matheus; Niedzielski, Daiane; Senhorini, Jose Augusto; Silva, Luciano Andrade; Nakaghi, Laura Satiko Okada [UNESP]; Yasui, George Shigueki (Elsevier B.V., 2020)
Gynogenesis is a chromosome manipulation technique applicable on the production of all-female populations, generation of inbred or clonal lines and identification of genetic sex determination mechanisms in fish. Therefore, the aim of this study was induce meiotic gynogenesis in Astyanax altiparanae and determine the genetic basis of sex determination. Firstly, we evaluated the best UV-irradiation dosage in order to inactivate sperm genome, preserving the capacity of egg activation without the genetic material contribution to the offspring. After the fertilization using the inactivated sperm, diplodization was achieved by heat-shock (40 degrees C; 2 min) by suppression of the 2nd polar body extrusion. Diploid control and gynogenetic individuals were raised until 240 days. The gynogenetic offspring were confirmed by genotyping using microsatellite markers and the sex ratio of gynogenetic progenies suggests that most data fit to a XX/XY model of sex determination. However, unexpected sex ratios were also observed and possible reasons are discussed. This was the first protocol of induced gynogenesis in a Neotropical fish and such a procedure may be used to produce clonal linage of fish and for future mass production of monosex populations in A. altiparanae and other related species.
Keywords: Chromosome set manipulation; Sex determination; Sex ratios; Microsatellite marker